The impact of training on operational performance: the case of the customs service at Nikola Tesla airport in Belgrade - Dalton, Sanja (Serbian Journal of Management, 2016)
In this paper the impact of risk analysis and assessment training of the customs officers on improvement of their operational performances at Nikola Tesla airport in Belgrade is presented. The aim of the research is to measure the perception of the customs officers at the airport about the operational effectiveness of the risk analysis training program. The research was conducted through survey, by collecting data from the questionnaire disseminated to the customs officers who were divided into experimental (the officers who attained the training) and control group (the officers who have not attained the training). Both groups of the officers evaluated the statements about their performance contribution in effective collection of revenue, facilitation of trade and passengers, border control and protection level and reputation of the customs unit at the airport. The results of the research show that there is a significant difference between the groups, which confirms the hypothesis that the risk analysis and assessment training has a positive impact on the customs officers’ operational efficiency.